The journey to the East - Hesse, Hermann, 1877-1962 (Picador, 2003)
A classic of modern literature, The Journey to the East is a profound rendering of the struggle between faith and despair. The hero, identified only as H.H., recounts a fantastic spiritual and geographic pilgrimage he took years ago with the League, a secret society whose members include the likes of Paul Klee, Mozart, and Baudelaire. Traversing both time and space, the pilgrims come across Noah's Ark in Zurich and meet Don Quixote at Bremgarten, only to part ways in seeming discord at the dangerous Morbio Gorge.